Pruebas de variedades de hortalizas en los Trópicos - Thomas, N.F. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
The Inter-American Institute of Agricultural Sciences has been testing local and imported vegetable varieties in Turrialba and Cartago, Costa Rica in an attempt to find the varieties best adapted to tropical conditions The vegetable varieties which have yield best of those tested in Turrialba include strains of Great Lakes and Impetial varieties of head lettuce, Black-Seeded Simpson and Slobolt loose-leaf lettuce, Louisiana Red Creole bulbing onion. Nebuka bunching onion, IALAS breeding lines of tomatoes, Jamaica (local) and Tendergreen varieties of snap beans, IAJAS Line A-65 sweet pepper, Rosita eggplant, Red Giant radish, Evergreen, Emerald, and Larga (local) varieties of okra, Purple Top White Globe tmnip; Italian Green Sprouting broccoli, Stein's Early Flat Dutch cabbage; Chibli chinese cabbage, Golden Plume celery, Fordbook Giant swiss chard; and Detroit Dark Red beet All sweet-potato varieties have been satisfactory but no watermelon or cauliflower varieties tested bave produced well in Imrialba.